Analysis of Void Growth and Coalescence in Porous Polymer Materials. Coalescence in Polymer Materials - Reffas, S. A.; Elmeguenni, M.; Benguediab, M. (Engineering, Technology & Applied Science Research, 2013)
The use of polymeric materials in engineering applications is growing more and more all over the world. This issue requests new methodologies of analysis in order to assess the material’s capability to withstand complex loads. The use of polyacetal in engineering applications has increased rapidly in the last decade. In order to evaluate the behavior, the damage and coalescence of this type of polymer, a numerical method based on damage which occurs following several stages (nucleation of cavities, their growth and coalescence in more advanced stages of deformation) is proposed in this work. A particular attention is given on the stress-strain and the volumetric strain evolution under different triaxiality and for three initial void shapes. Its application to polyacetal allows approving this approach for technical polymers. Finally, this method allow us to compare the obtained results of basic calculations at different triaxiality and to discuss their possible influence on the initial size and the geometrical shape of the porosity on the material failure.